Pengaruh Model Case Based Learning terhadap Kemampuan Menulis Teks Cerpen Siswa Kelas XI SMK YAMPIM BIRU-BIRU - Putri Dinda Resta Silaban; Elly Prihasti Wuriyani (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to determine the effect of the Case Based Learning learning model on the ability to write short story texts in class XI of YAPIM BIRU-BIRU Vocational School. The population of this study involved all students in class XI TKJ SMK YAMPIM BIRU-BIRU totaling 121 students, using a simple random sampling technique. The sample in this study consisted of 30 students in the control class using the conventional model, and 30 students in the experimental class using the Case Based Learning model. The research method used is a quantitative experimental research method. The instrument used is a description test instrument. Data collection in this research was obtained through tests on student learning outcomes in writing short story texts. Based on the test results, the results of this research can be concluded as follows. First, the ability to write short story texts using conventional models in class XI TKJ-2 is in the very low category with a percentage of 53.5 out of 30 students. Second, the ability to write short story texts using the Case Based Learning model in class XI TKJ-2 is in the very good category with a percentage of 83.83 out of 30 students. Thus, it can be said that the score for the ability to write short story texts in the experimental class is higher than in the control class. Third, through hypothesis testing, it shows that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha), because the calculated t is greater than the t table, namely 11.864, greater than 1.699. Thus, it can be concluded that the Case Based Learning model influences the ability to write short story texts for class XI TKJ SMK YAPIM BIRU-BIRU.